2021
DOI: 10.1002/jcop.22629
|View full text |Cite
|
Sign up to set email alerts
|

Developing strategies to improve the community readiness level to prevent drug abuse in adolescents: Based on the community readiness model, Eghlid City, Iran, 2019

Abstract: The aim of this study was to investigate the level of readiness of Eghlid city community for adolescents' substance abuse prevention programs, and to develop strategies to improve community readiness levels based on the community readiness model (CRM). In this two-stage qualitative study, a 36-item semi-structured CRM questionnaire, was used to interview 11 key informants in Eghlid city, Iran, 2019. The interviews were analyzed and scored by two independent researchers. Strategies for increasing the level of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…This result corresponds with the findings of Coroiu et al [71] and Kostadinov et al [72]. However, some previous studies found that the dimension of community efforts received the highest scores in both Western settings, such as the UK and the USA, and in the Middle East context, such as Iran [73]. A possible explanation for the different results may be that community leaders in China played an irreplaceable and vitally important role in the process of combating COVID-19, through following the leadership of the Communist Party of China, implementing epidemic prevention and control policy promulgated by the government, and mobilizing community residents to participate.…”
Section: Discussionsupporting
confidence: 91%
“…This result corresponds with the findings of Coroiu et al [71] and Kostadinov et al [72]. However, some previous studies found that the dimension of community efforts received the highest scores in both Western settings, such as the UK and the USA, and in the Middle East context, such as Iran [73]. A possible explanation for the different results may be that community leaders in China played an irreplaceable and vitally important role in the process of combating COVID-19, through following the leadership of the Communist Party of China, implementing epidemic prevention and control policy promulgated by the government, and mobilizing community residents to participate.…”
Section: Discussionsupporting
confidence: 91%
“…The problem discussed was wild grazing by farmers. Ghahremani et al (2021) stated that strategic development could be carried out by holding training programs, local media, and lectures in developing existing resources. As a result, farmers will get some information about the impact caused by wild grazing.…”
Section: Discussionmentioning
confidence: 99%
“…Farmer's participation in the intensification program plan can affect the program's success rate. A community readiness assessment is a fundamental step in preparing several actions to take approaches that follow the socioeconomic aspect (Ghahremani et al 2021). The study assessed the community readiness for the intensification program to reduce wild grazing in BNP.…”
Section: Introductionmentioning
confidence: 99%